The cutting edge : conserving wildlife in logged tropical forest - Fimbel, Robert A.; Grajal, Alejandro; Robinson, John G. (Biology and resource management in the tropics series., 2001)
Recent decades have seen unprecedented growth in the scale and intensity of industrial forestry. Directly and indirectly, it has degraded the wildlife and ecological integrity of these tropical forests, prompting a need to evaluate the impact of current forest management practices and reconsider how best to preserve the integrity of the biosphere. Synthesizing the body of knowledge of leading scientists and professionals in tropical forest ecology and management, this book's thirty chapters examine in detail the interplay between timber harvesting and wildlife, from hunted and pr.